PENGARUH KEPEMILIKAN SEKURITAS MAYORITAS DAN STRATEGI TERHADAP KINERJA KEUANGAN - Agus Munandar; Dara Putri Junianti; Eka Setiawati; Novita Rahmawati Putri; Salwa Latifa Putri (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2022)
Abstract The majority of company ownership in Indonesia is concentrated, this triggers expropriation by the majority shareholders over minority shareholders. For this reason, this research focuses on majority share ownership, company strategy, and the financial performance of companies listed on the Indonesia Stock Exchange (IDX). This study aims to examine the influence of the majority shareholding structure and corporate strategy on financial performance as measured using return on assets (ROA), return on equity (ROE) and net profit margin (NPM). The sample of this research is a company in the investment banking and trade intermediary industrial sector, totaling 5 companies with the 2017-2020 period. This research method uses descriptive statistics and regression. Sample data obtained from the company's annual report. This study shows that the strategy has a positive effect on ROA, ROE, and NPM. The majority ownership has a negative effect on ROA, ROE and NPM. Keywords: Profitability, Majority Ownership, Financial Performance